Translation, cross-cultural adaptation and validation of the Short Screening Instrument for Psychological Problems in Enuresis for use in Brazil (SSIPPE-Br) - Gláucia Cristina Medeiros Dias; Mônica Maria de Almeida Vasconcelos; José Murillo Bastos Netto; Débora Marques de Miranda; Eleonora Moreira Lima; Ana Cristina Simões e Silva; Janaina Matos Moreira; Flávia Cristina de Carvalho Mrad (Jornal de Pediatria, 2024)
Objective: Enuresis is associated with attentional and emotional comorbidities in 20 to 30 % of cases. The Short Screening Instrument for Psychological Problems in Enuresis (SSIPPE) is a questionnaire that allows the initial screening of these comorbidities. This study aimed to translate, culturally adapt, and validate the SSIPPE for Brazilian children and adolescents (SSIPPE-Br). Methods: Six steps were performed for translation and cross-cultural adaptation: translation, synthesis of translations, back-translation, preparation of the pre-final version of the translated instrument, test of comprehensibility of the pre-final version of the tool, and elaboration of the instrument cross-culturally adapted for Brazil, named 13-itens version SSIPPE-Br. To validate the SSIPPE-Br, a cross-sectional study was carried out, in which the validated Brazilian version of the Child and Adolescent Behavior Inventory (CABI) was used. Results: Validation was performed on 127 children and adolescents with a mean age of 9.7 ± 2.8 years, 48 % male. The reliability was estimated using Cronbach's alpha, ranging from 0.86 to 0.89, indicating good internal consistency. The factorial analysis had a good agreement adjustment (KMO 0.755, Bartlett's test < 0.001) and explained 70.5 % of the data variability. In the reproducibility analysis, the Kappa coefficient ranged from 0.94 to 1, which can be considered almost perfect. A highly significant (p-value < 0.001) and direct correlation existed between the three SSIPPE-Br domains and all evaluated CABI domains. Conclusion: The SSIPPE-Br is a valid and reliable tool for emotional problems screening and ADHD symptoms in children and adolescents with enuresis whose first language is Brazilian Portuguese.